LEGAL ASPECTS IN MANAGEMENT OF HAZARDOUS AND TOXIC WASTE - Wahyu Yun Santosa (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2017)
AbstractHazardous and Toxic Waste (B3 in Indonesian abbreviation) have specific types and characteristics which could harm the environment itself and/or human health and other living being if thrown away to the environmental medium without proper treatment. On this basis, integrated hazardous waste treatment is needed to be regulated in a regulatory framework. Indonesian environmental law regime under Law no 32/2009 (EPMA) has given an integrated regulatory framework which intertwined every knot of hazardous and toxic waste treatment, including: containment, collecting, transporting, treatment, reuse, and dumping by Government Regulation No 101 year 2014. This article briefly explains the hazardous and toxic waste integrated treatment in Indonesia, both from the regulatory framework perspective and from environmental law aspect analysis.IntisariLimbah Bahan Berbahaya dan Beracun atau limbah B3 memiliki sifat dan karakteristik tersendiri yang dapat menimbulkan bahaya terhadap lingkungan hidup itu sendiri maupun kesehatan manusia serta makhluk hidup lainnya apabila dibuang langsung ke dalam media lingkungan hidup. Atas pertimbangan itulah, pengelolaan limbah B3 menjadi suatu kewajiban untuk diatur di dalam kerangka perundang-undangan. Rejim hukum lingkungan berdasarkan UU 32/2009 (UUPPLH) memberikan pengaturan secara terpadu yang menghubungkan keterkaitan setiap simpul Pengelolaan Limbah B3 yaitu kegiatan penyimpanan, pengumpulan, pengangkutan, pengolahan, pemanfaatan, dan penimbunan limbah B3 melalui PP Nomor 101 Tahun 2014. Artikel ini memaparkan secara ringkas konsep pengelolaan limbah B3 baik dalam kerangka pengaturan yang ada serta dengan analisis dari aspek hukum lingkungan yang terkait di dalam pengelolaan limbah B3 secara terpadu.